Evaluation of grit and its associated factors among undergraduate pharmacy students from 14 Asian and Middle Eastern countries amid the COVID-19 pandemic - Mohamed Hassan Elnaem; Muna Barakat; Naeem Mubarak; Mohammed Salim K.T.; Doaa H. Abdelaziz; Ahmed Ibrahim Fathelrahman; Abrar K. Thabit; Diana Laila Ramatillah; Ali Azeez Al-Jumaili; Nabeel Kashan Syed; Mohammed Fathelrahman Adam; Md. Sanower Hossain; et al. (Saudi Pharmaceutical Journal, 2023)
Introduction: Grit is proposed as an essential trait for academic achievement. Thus, evaluating its current status and the associated factors could aid academic support planning. Objective: The present study aimed to assess grit level and its related factors among undergraduate pharmacy students from 14 countries amid the COVID-19 pandemic. Methods: A cross-sectional survey-based study was conducted among pharmacy students from 14 countries in Asia and the Middle East. A 31-item questionnaire was developed, validated, and pilot-tested, including the validated short scale for grit assessment. The data was collected between 1 February and 15 April 2022. Descriptive and inferential statistics were employed as appropriate. Results: A total of 2665 responses were received, mainly from females (68.7 %), living in urban areas (69.2 %) and studying at private universities (59.1 %). The average grit score on a scale of 5 was 3.15 ± 0.54. The responses revealed higher favourable responses to items on the perseverance of efforts (34.9 % to 54 %) compared to items on the consistency of interests (26.5 % to 31.1 %). Students who did not exercise (AOR: 0.47, 95 %CI: 0.33–0.67) or exercised irregularly (AOR: 0.64, 95 %CI: 0.45–0.90) were less likely to have higher grit scores than those who exercised regularly. Additionally, students who did not receive COVID-19 vaccination (AOR: 0.50, 95 %CI: 0.36–0.71) or received only one dose (AOR: 0.67, 95 %CI: 0.46–0.99) were less likely to have higher grit scores than those who received their booster vaccination. Interestingly, students who chose the pharmacy program as their only available or reasonable choice (AOR: 0.33, 95 %CI: 0.17–0.62) and students from public universities (AOR: 0.82, 95 %CI: 0.68–0.98) were less likely to have higher grit scores. On the other hand, students who did not face educational challenges with online learning (AOR: 1.19, 95 %CI: 1.003–1.416) and students with excellent (AOR: 2.28, 95 %CI: 1.57–3.31) and very good (AOR: 2.16, 95 %CI: 1.53–3.04) academic performance were more likely to have higher grit scores. Conclusion: The findings revealed moderate grit levels. Higher grit levels were thought to be associated with several personal, lifestyle and academic factors. Further interventions to support students' grit attributes are required, particularly concerning the consistency of interests.